Reproducibility of an incremental treadmill Vo2max test with gas exchange analysis for runners - LourenÇo, T. F.; Martins, L. E. B.; Tessutti, L. S.; Brenzikofer, R.; Macedo, D. V. (The Journal of Strength and Conditioning Research, 2011)
The evaluation of performance through the application of adequate physical tests during a sportive season may be a useful tool to evaluate training adaptations and determine training intensities. For runners, treadmill incremental VO2max tests with gas exchange analysis have been widely used to determine maximal and submaximal parameters such as the ventilatory threshold (VT) and respiratory compensation point (RCP) running speed. However, these tests often differ in methodological characteristics (e.g., stage duration, grade, and speed increment size), and few studies have examined the reproducibility of their protocol. Therefore, the aim of this study was to verify the reproducibility and determine the running speeds related to maximal and submaximal parameters of a specific incremental maximum effort treadmill protocol for amateur runners. Eleven amateur male runners underwent 4 repetitions of the protocol (25-second stages, each increasing by 0.3 km/h in running speed while the treadmill grade remained fixed at 1%) after 3 minutes of warm-up at 8-8.5 km/h. We found no significant differences in any of the analyzed parameters, including VT, RCP, and VO2max during the 4 repetitions (p > 0.05). Further, the results related to running speed showed high within-subject reproducibility (coefficient of variation < 5.2%). The typical error (TE) values for running speed related to VT (TE = 0.62 km/h), RCP (TE = 0.35 km/h), and VO2max (TE = 0.43 km/h) indicated high sensitivity and reproducibility of this protocol. We conclude that this VO2max protocol facilitates a clear determination of the running speeds related to VT, RCP, and VO2max and has the potential to enable the evaluation of small training effects on maximal and submaximal parameters.